Rwanda Economic Update, June 2018 : Tackling Stunting - An Unfinished Agenda - World Bank Group (World Bank, Washington, DC, 2018)
Rwanda's economy rebounded in the second half of 2017. The rebound, driven by improved exportperformance and revitalized agriculture, pushed annual growth to 6.1 percent and led to upwardrevisions of the growth projections for 2018 and 2019. However, although growth is currently recovering and is more balanced, it will most likely continue to be below the high rates achieved during the 2013–15 investment push.